The Impact of Conflicts of Interest on the Developments of the Elections Law of the Islamic Consultative Assembly: A Case Study of the Conditions for Candidates - Alireza Mazinani; Mohammad Bahadori Jahrami; Mohammad Shabani Jahrami (دانش حقوق عمومی)
The Elections Law of the Islamic Consultative Assembly is unparalleled in terms of the number of changes made to it throughout the history of legislation in Iran. A common point among many of these changes is the expansion of the circle of those disqualified from candidacy in elections. Given that most representatives in each legislative term run for election in the next term, there arises a suspicion regarding the impact of conflicts of interest on these changes. This research, conducted through a descriptive-analytical method with a legal perspective, seeks to answer the question of what role conflicts of interest have played in the legislative changes affecting the conditions for candidates in the elections of the Islamic Consultative Assembly. The findings indicate that many of the positive and negative conditions for candidates added to the Elections Law over the past four decades are stringent and are either rare or unique compared to electoral laws in other countries. In practice, it seems that some of these conditions have not significantly contributed to the selection of qualified candidates; instead, they have unjustifiably disqualified many capable individuals from running for election. Considering this evidence and indications, it can be asserted that conflicts of interest may indeed be one of the main factors influencing changes in the Elections Law of the Islamic Consultative Assembly. Many representatives over various terms have sought to eliminate their competitors from the electoral scene by establishing unreasonable conditions for candidates.